Death & sensibility - Blake, Elizabeth (Novelist) (Blake, Elizabeth. Jane Austen Society mystery., 2021)
"The owner of a bookstore investigates after the keynote speaker at the Jane Austen Society conference she's hosting turns up dead of a suspicious heart attack in the second addition to the series following Pride, Prejudice and Poison"--